(untitled) (Studia Prawnicze / The Legal Studies, 2012)
W kwietniu 2011 r. uchwalono Konwencję Rady Europy w sprawie zapobiegania i zwalczania przemocy wobec kobiet i przemocy domowej, traktat który ma szansę stać się najważniejszym instrumentem międzynarodowym w dziedzinie zwalczania przemocy wobec kobiet. Niniejszy artykuł ma na celu dokonanie analizy zobowiązań, które Konwencja nakłada na państwa-strony, w tym zasygnalizowanie najważniejszych konsekwencji wynikających dla prawa polskiego w przypadku przystąpienia Polski do Konwencji. Pomimo udziału w procesie przygotowania tej umowy międzynarodowej, Polska nie znalazła się w gronie jej sygnatariuszy. Choć kwestia przystąpienia do Konwencji wywołuje kontrowersje wewnątrz samego rządu, składane są jednoznaczne deklaracje, iż zostanie ona ratyfikowana. Violence against women, in particular domestic violence, is a form of discrimination against women and a human rights violation, which has been voiced in recent years by international human rights bodies, including the UN Committee on the Elimination of Discrimination against Women and the European Court of Human Rights. The Council of Europe Convention on preventing and combating violence against women and domestic violence, which was adopted on 7th April 2011, derives from this output. The Convention, being a milestone in combating violence against women, creates a comprehensive legal framework to prevent violence, to protect victims and to end with the impunity of perpetrators. The paper aims to examine and clarify the main obligations of the State Parties to this treaty. The core part of the study analyzes the obligation to define and criminalise various forms of violence against women (such as physical, psychological and sexual violence, stalking, forced marriage, female genital mutilation, forced abortion and forced sterilisation, sexual harassment). It also focuses on obligations linked to investigation and prosecution of these crimes. Special attention is paid to protective measures such as restraining or protection orders. Another major objective of the paper is to indicate the most significant consequences to the Polish legal order in case of Poland’s accession to the treaty. Despite taking part in the drafting process, Poland did not finally sign up the Convention. However, the Polish government takes into account a possibility of its ratification. In Author’s opinion, Poland’s accession to this treaty is highly advisable. What is more, only few provisions of the present Polish law would demand to be conformed to the Convention.